Making use of Home Equity - Holzmann, Robert (2019)
Holzmann, R., Ayuso, M., & Bravo, J. M. (2019). Making use of Home Equity: The Potential of Housing Wealth to Enhance Retirement Security. (IZA Discussion Papers; No. 12656). IZA. Institute of Labor Economics.